Why aid diplomacy eventually pays off: Lessons from Australia’s Demonstration Sheep Farm Project in 1970s South Korea - Park, Hea-jin; Elfving-Hwang, Jo; Whitney, Younghye Seo (2022)
When two Kelpie sheepdogs and the first consignment of 2,500 Australian sheep arrived in a remote Korean village of Unbong in the summer of 1972, few would have imagined it would lay the foundations for one of the most successful yet forgotten episodes in Australian aid diplomacy.